127k views
4 votes
Solve the differential equation dy dx + 12x2y = 36x2. SOLUTION The given equation is linear since it has the form of this equation with P(x) = 12x2 and Q(x) = 36x2. An integration factor is I(x) = e∫12x2 dx = .

1 Answer

4 votes

Answer:

Therefore the solution of the differential equation is


ye^(4x^3) = 3e^(4x^3)+c [ where c is arbitrary constant]

Explanation:

Given differential equation is


(dy)/(dx) +12x^2y= 36x^2

Here
P(x)= 12x^2 and
Q(x) = 36 x^2

The integrating factor of the differential equation is


= e^{\int P(x) dx


=e^{\int 12x^2dx


=e^{ (12x^3)/(3)}


=e^(4x^3)

Multiplying the integrating factor both sides of the differential equation


e^(4x^3)(dy)/(dx) +12x^2ye^(4x^3)= 36x^2e^(4x^3)


\Rightarrow e^(4x^3) dy+12x^2ye^(4x^3)dx= 36x^2e^(4x^3)dx

Integrating both sides,


\int e^(4x^3) dy+\int12x^2ye^(4x^3)dx= \int36x^2e^(4x^3)dx......(1)

Let


I= \int36x^2e^(4x^3)dx


= \int3. 12 x^2e^(4x^3)dx

putting
{4x^3}=z ,
12x^2 dx=dz


=\int 3. e^zdz


=3e^z+c [ where c is arbitrary constant]

Putting the value of z


=3e^(4x^3)+c

From (1) we get


\int e^(4x^3) dy+\int12x^2ye^(4x^3)dx= \int36x^2e^(4x^3)dx


\Rightarrow ye^(4x^3) = 3e^(4x^3)+c

Therefore the solution of the differential equation is


ye^(4x^3) = 3e^(4x^3)+c [ where c is arbitrary constant]

User Norayr Ghukasyan
by
4.5k points